ANALISIS PENGARUH PERTUMBUHAN EKONOMI DAN INVESTASI TERHADAP TINGKAT PENGANGGURAN TERBUKA PROVINSI BALI 2019-2022 - Syach, Ariq Athira; Badriyah, Nurul (Journal of Development Economic and Social Studies, 2024)
The purpose of this study is to analyze the effect of investment and economic growth on the open unemployment rate in Bali Province in 2019-2022. This research uses quantitative research methods and multiple linear regression analysis methods. The research uses secondary data sourced from the central statistics agency and the investment coordinating agency and panel data methods. The results of the study show that economic growth has a significant and negative effect on the level of open unemployment; This means that an increase in economic growth causes a decrease in the unemployment rate, whereas if economic growth decreases it causes the unemployment rate to decrease. Furthermore, investment has an insignificant and positive effect on the unemployment rate; This means that an increase in the investment value causes the unemployment rate to increase, whereas if there is a decrease in the investment value it causes the unemployment rate to decrease.